Inspecting the impact of financial inclusion on emissions in India: The banking channel - Saon Ray; Vasundhara Thakur (Indian Council for Research on International Economic Relations (ICRIER), 2025)
The urgent need to address climate change has placed environmental degradation and sustainable development at the centre of policy discussions. This highlights the importance of examining how the financial system directs funds toward green investments or emission-intensive industries. Expanding financial inclusion integrates more individuals into the formal financial system, influencing capital allocation. India has introduced several initiatives in recent years to enhance financial inclusion. In this context, this study explores the impact of financial inclusion on carbon emissions in India from 1990 to 2018. It also examines the interplay of financial inclusion and financial development on carbon emissions in India. The study uses the ARDL bounds testing approach to find a long-run relationship between financial inclusion and carbon emissions. However, the interaction between financial inclusion and financial development does not significantly impact emissions in the long run. These findings contribute to understanding the role of financial inclusion in shaping India's environmental trajectory.
Keywords: O16; G21; E51; Q56; 330; financial inclusion; carbon emissions; financial development; banking; green finance